Optimization of reaction conditions by detailed cycle simulation of thermo-chemical air separation for high-purity nitrogen production using the perovskite oxide SrFeO3 - Katrin Klingel; Lena Klaas; Nicole Neumann; Mathias Pein; Martin Roeb; Christian Sattler (Chemical Engineering Journal, 2026)

Development and analysis of a SmPC-based machine-readable dataset of contraindications for clinical decision support and real-world data analysis - Miriam Schechner; Wahram Andrikyan; Thomas Bauerdick; Theresa Terstegen; Louisa Redeker; Martin Federbusch; Katrin Farker; Alexander Strübing; Florian Schmidt; Petra Thürmann; Sven Schmiedl; Hanna M. Seidling; et al. (European Journal of Clinical Pharmacology, 2026)
Purpose Unrecognized contraindications pose risks for adverse drug reactions, hospitalizations or death. Clinical decision support systems (CDSS) aim to mitigate medication-related harm, particularly originating from contraindications. However, many CDSS provide limited benefit, as they focus largely on singular risk situations such as drug-drug interactions and often generate alerts of limited clinical relevance. Comprehensive integration of contraindications into CDSS may support more clinically meaningful alerts. The aim of this work was the development and analysis of machine-readable contraindication lists, including drug-clinical condition, drug-kidney function and drug-drug (group) contraindications, for integration into CDSS and real-world data analysis. Methods We extracted and operationalized contraindications, based on Summaries of Product Characteristics (SmPCs), of the 688 most prescribed drugs in Germany, leveraging common medical coding systems. Moreover, we analyzed extracted contraindications based on operationalizability, overall frequency and frequencies within different contraindication categories. Results In total, we extracted 4676 contraindications, of which 2129 (45.5%) were deemed operationalizable. Of these 2129 contraindications, 1652 (77.6%) were attributed to drug-clinical condition, 83 (3.9%) to drug-kidney, 140 (6.6%) to drug-drug group and 254 (11.9%) to drug-drug. The most frequently mentioned contraindicated risk situations were ‘severe liver insufficiency’ ( n = 74, 3.5%), ‘pregnancy’ ( n = 66, 3.1%), ‘MAO-inhibitors’ ( n = 44, 2.1%), and ‘shock’ ( n = 44, 2.1%). Conclusion Our results show, that drug-clinical condition contraindications are listed far more frequently in SmPCs than other contraindication categories. Focusing on clinical condition-related contraindications within CDSS could improve the detection of clinically relevant contraindications in routine data and enhance medication safety. The clinical applicability is currently being evaluated in the INTERPOLAR study.

Temperate Forest Floors: Ecosystem Hubs in Transition? - Friederike Lang; Jörg Prietzel; Frank Hagedorn; Klaus Kaiser; Stefanie Schulz; Mathias Mayer; Lars Vesterdal; Jürgen Bauhus; Maï Bergmann; Sebastian Bibinger; Martin I. Bidartondo; Jingxuan Olivia Chen; et al. (Global Change Biology, 2026)
The forest floor (FF) plays a key role in carbon, nutrient, and water cycling. It is the biologically most active compartment of forest soils, highly responsive to environmental conditions. Yet, its response to current changes in environmental conditions and forest management is understudied. Temperate forests are among the best studied ecosystems globally, providing the necessary ecological and biogeochemical background information to assess FF changes. Here, we focus on identifying existing knowledge and gaps in our understanding of the functioning of the FF. Interactions between FF biota and abiotic FF components show multifactorial dependencies with environmental conditions and drive FF turnover. Vice versa, the turnover of FF regulates carbon, nutrient, and water cycling. With slow litter decomposition and limited bioturbation, organic matter accumulates, nutrients cycle tightly within the FF, and water passes through this layer partly along preferential pathways. With rapid litter decomposition and intense bioturbation, FF accumulation is little, the mineral soil is the main nexus for plant nutrient uptake and organic matter transformation, and water infiltrates the mineral soil more homogeneously. The interconnectedness with the adjacent ecosystem compartments is a crucial feature of the FF, feeding back to its functioning and making it a central hub of forest processes. The FF morphology reflects these processes and therefore has untapped potential as an indicator of soil and ecosystem health. Under forest change, the FF might lose its functionality, with negative impacts on nutrient provision, water storage, and carbon sequestration. Consequences for forest growth could be strong and even detrimental. Hence, improved knowledge of FF characteristics and their linkages to mineral soils and aboveground ecosystem compartments is crucial for assessing forest resilience to progressing environmental changes.

Assessment of the welfare of the police horses based on salivary cortisol levels during the special search operations - Martina Janošíková; Kristýna Petričáková; Cyril Neumann; Ivona Svobodová; Hana Süssenbeková; Martin Ptáček; Petr Denk (Applied Animal Behaviour Science, 2026)

Microzooplankton in the Equatorial Southwestern Atlantic: establishing a baseline for a changing ocean - Ana Cecília Pinho Costa; José Pedro Vieira Arruda Júnior; Letícia Borges Leite; Tatiane Martins Garcia; Sigrid Neumann-Leitão; Marcelo Oliveira Soares (Regional Studies in Marine Science, 2026)

Influence of Tryptophan Metabolism on the Protective Effect of Weissella paramesenteroides WpK4 in a Murine Model of Chemotherapy-Induced Intestinal Mucositis - Gabriele Moreira Guimarães; Karen Costa; César da Silva Santana Moura; Sarah Elisa Diniz Moreira; Joana Mozer Marchiori; Anna Clara Paiva de Menezes Santos; Rafaela Ribeiro Alvares Batista; Celso Martins Queiroz-Junior; Juliana Divina Almeida Raposo; Fernão Castro Braga; Marcelo Vidigal Caliari; Álvaro Cantini Nunes; et al. (Probiotics and Antimicrobial Proteins, 2025)

On the origin of the late-flowering ppd-H1 allele in barley - Rajiv Sharma; Salar Shaaf; Kerstin Neumann; Peter Civan; Yu Guo; Martin Mascher; Michal David; Adnan Al-Yassin; Hakan Özkan; Tom Blake; Sariel Hübner; Nora P. Castañeda-Álvarez; et al. (Theoretical and Applied Genetics, 2025)
To breed for climate resilient crops, an understanding of the genetic and environmental factors influencing adaptation is critical. Barley provides a model species to study adaptation to climate change. Here we present a detailed analysis of genetic variation at a major photoperiod response locus and relate this to the domestication history and dispersal of barley. The PPD-H1 locus (a PSEUDO-RESPONSE REGULATOR 7 ) promotes flowering under long-day conditions, and a natural mutation at this locus resulted in a recessive, late-flowering ppd-H1 allele. This mutation proved beneficial in high-latitude environments such as Northern Europe, where it allows extended vegetative growth during long spring days. We infer the origin of the mutated late-flowering ppd-H1 allele by re-sequencing a large geo-referenced collection of 942 Hordeum spontaneum , 5 Hordeum agriocrithon and 1110 domesticated ( Hordeum vulgare ) barleys. We demonstrate that the late-flowering phenotype originated from Desert-type wild barley in the Southern Levant and present evidence suggesting a post-domestication origin of the mutated ppd-H1 allele.

Unravelling sources of fecal pollution in oligotrophic mountain waters: Integrating Escherichia coli enumeration, microbial source tracking, and eDNA analysis - Sharon Maes; Martin Andersson-Li; Jessica Sjöstedt; Jon Hildahl; Daniel Yu; Norman Neumann; Monica Odlare; Anders Jonsson (Environmental Monitoring and Assessment, 2025)
Aquatic ecosystems in mountainous regions are crucial for fulfilling natural and anthropogenic water demands around the world. This study integrates Escherichia coli ( E. coli ) enumeration, microbial source tracking (MST), and environmental DNA (eDNA) analysis to identify sources of fecal contamination in oligotrophic mountain waters. Conducted in an area with intense tourism and traditional reindeer herding, this research addresses the urgent need to identify fecal pollution sources to safeguard the water quality of these vital ecosystems. Our study reveals that E. coli levels vary significantly across different locations and times, suggesting varied sources of contamination from humans, wildlife, and livestock animals. MST techniques, alongside eDNA analysis, provided insights into the complex patterns of fecal pollution, allowing for the distinction between human and animal contributions to water contamination. Our findings highlight the importance of combining various analytical methods to track fecal pollution sources effectively, and to develop targeted strategies for water quality management.

From molecular to immuno-pharmacology: Schmiedeberg Medal for Klaus Resch - Michael U. Martin; Detlef Neumann; Michael Kracht (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

First subfossil Holocene avian breeding burrows in volcanic rocks of the Tibesti Mountains (Chad) - Jens Hering; Heidi Hering; Martin Winter; Stefan Kröpelin; Peter H. Barthel; Christian Neumann (Journal of Ornithology, 2025)

Semi-variograms provide superior spatial and temporal insights into artificial rainfall compared to Christiansen uniformity - Jan-František Kubát; Martin Neumann; Petr Kavka (Journal of Hydrology, 2025)

Aquirufa esocilacus sp. nov., Aquirufa originis sp. nov., Aquirufa avitistagni, and Aquirufa echingensis sp. nov. discovered in small freshwater habitats in Austria during a citizen science project - Alexandra Pitt; Stefan Lienbacher; Johanna Schmidt; Meina Neumann-Schaal; Jacqueline Wolf; Aharon Oren; Sophia Reichl; Martin W. Hahn (Archives of Microbiology, 2025)
Within a citizen science project, 112 freshwater habitats in Austria were sampled to get bacterial cultures belonging to the genus Aquirufa using a strategy for targeted isolation. We focused on these bacteria because they are widespread and represent typical freshwater bacteria and, furthermore, the typic red pigmentation facilitates preselection. Among the 113 obtained Aquirufa strains were HETE-83D T , KTFRIE-69F T , OSTEICH-129V T and PLAD-142S6K T , originating from small ponds and a creek. Phylogenetic reconstructions with 16S rRNA gene sequences and genome-based analyses with amino acid sequences of 501 core genes showed that all four strains belonged to the A. antheringensis branch of the genus Aquirufa . Calculation of whole-genome average nucleotide identity values and digital DNA-DNA hybridization values revealed that they represent in each case a new species. The genome sizes of the four strains were between 2.5 and 2.8 Mbp and the G + C values were between 41.4 and 41.8%. Like all type strains of the genus Aquirufa , cells were rod-shaped, and liquid cultures and colonies on agar plates were red-pigmented, likely due to carotenoids. All strains except OSTEICH-129V T showed gliding motility on soft agar plates. All strains grew aerobically but only PLAD-142S6K T could grow weakly under anaerobic conditions. We propose here to establish the names Aquirufa esocilacus sp. nov. for strain HETE-83D T (= DSM 118087 T = JCM 37094 T ), Aquirufa originis sp. nov. for KTFRIE-69F T (= DSM 117798 T = JCM 37095 T ), Aquirufa avitistagni for OSTEICH-129V T (= DSM 118088 T = JCM 37100 T ) and Aquirufa echingensis sp. nov. for PLAD-142S6K T (= DSM 117799 T = JCM 37096 T ).

Mobility of Sediment and Phosphorus in a Small Stream During Artificial Flood Wave - Martin Neumann; Barbora Jáchymová; Petr Koudelka; Tomáš Dostál; Miroslav Bauer; Josef Krása; Tomáš Laburda; Pavel Rosendorf; Daniel Fiala; Karina Bynum; John S. Schwartz; David Zumr (Environmental Processes, 2025)
This study investigates the dynamics of sediment and phosphorus transport in small streams affected by recurrent flood waves. The experiments were carried out in two streams with contrasting conditions: one in an agricultural headwater section, which serves as a sediment source, and the other in a mid-water section influenced by fish ponds. High-frequency data on suspended sediment and phosphorus concentrations were collected during several flood waves to assess how floods affect the transport regime, including the role of small reservoirs. The results showed that even initially clear water can mobilize significant amounts of sediment from the riverbed when discharge increases. Sediment mobilization was strongest at the beginning of the flood wave, with concentrations peaking early and then decreasing. Successive floods without additional sediment input led to a decrease in sediment concentrations, as the stream had already flushed out the available sediments. Hysteresis loops showed that most of the sediment transport occurred during the rising part of the flood wave, indicating that the sediment originated from the nearby streambed areas. Phosphorus was mobilized simultaneously with the sediment, and an almost linear relationship was observed between sediment concentration and total phosphorus ( r = 0.979, p < 0.0001). However, only a fraction of the phosphorus was dissolved, so most of the phosphorus was bound to the sediment particles. Soluble reactive phosphorus showed a weaker correlation with sediment concentration ( r = 0.272, p = 0.047). This shows how important it is to consider both sediment dynamics and phosphorus mobilization in event-based flood models.

A quantitative modeling framework to understand the physiology of the hypothalamic-pituitary-adrenal axis and interaction with cortisol replacement therapy - Davide Bindellini; Robin Michelet; Linda B. S. Aulin; Johanna Melin; Uta Neumann; Oliver Blankenstein; Wilhelm Huisinga; Martin J. Whitaker; Richard Ross; Charlotte Kloft (Journal of Pharmacokinetics and Pharmacodynamics, 2024)
Congenital adrenal hyperplasia (CAH) is characterized by impaired adrenal cortisol production. Hydrocortisone (synthetic cortisol) is the drug-of-choice for cortisol replacement therapy, aiming to mimic physiological cortisol circadian rhythm. The hypothalamic-pituitary-adrenal (HPA) axis controls cortisol production through the pituitary adrenocorticotropic hormone (ACTH) and feedback mechanisms. The aim of this study was to quantify key mechanisms involved in the HPA axis activity regulation and their interaction with hydrocortisone therapy. Data from 30 healthy volunteers was leveraged: Endogenous ACTH and cortisol concentrations without any intervention as well as cortisol concentrations measured after dexamethasone suppression and single dose administration of (i) 0.5–10 mg hydrocortisone as granules, (ii) 20 mg hydrocortisone as granules and intravenous bolus. A stepwise model development workflow was used: A newly developed model for endogenous ACTH and cortisol was merged with a refined hydrocortisone pharmacokinetic model. The joint model was used to simulate ACTH and cortisol trajectories in CAH patients with varying degrees of enzyme deficiency, with or without hydrocortisone administration, and healthy individuals. Time-dependent ACTH-driven endogenous cortisol production and cortisol-mediated feedback inhibition of ACTH secretion processes were quantified and implemented in the model. Comparison of simulated ACTH and cortisol trajectories between CAH patients and healthy individuals showed the importance of administering hydrocortisone before morning ACTH secretion peak time to suppress ACTH overproduction observed in untreated CAH patients. The developed framework allowed to gain insights on the physiological mechanisms of the HPA axis regulation, its perturbations in CAH and interaction with hydrocortisone administration, paving the way towards cortisol replacement therapy optimization. Graphical Abstract

Trace element partitioning between natural barite and deep anoxic groundwaters: Implications for radionuclide retention in host rocks of nuclear waste repositories - Ferdinand Kirchner; Martin Kutzschbach; Henrik Drake; Vanessa Fichtner; Piotr M. Kowalski; Stefan Rudin; Martin J. Whitehouse; Mikael Tillberg; Thomas Neumann (Applied Geochemistry, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

TGFβ signalling pathway impacts brain metastases profiles in locally advanced colorectal cancer - Sven Jacob; Ilja Balonov; Vindi Jurinovic; Christian Heiliger; Tengis Tschaidse; Jörg Kumbrink; Thomas Kirchner; Jens Werner; Martin K. Angele; Marlies Michl; Jens Neumann (Clinical & Experimental Metastasis, 2024)
Rationale Colorectal Cancer (CRC) represents the third most common type of cancer in Germany and the second most common cancer-related cause of death worldwide. Distant metastases are still the main limit for patient survival. While liver metastases as well as peritoneal carcinomatosis can often either be resected or treated with systemic therapy, little options remain for brain metastases. Additionally, a number of studies has already investigated hepatic, peritoneal, pulmonary as well as continuing distant metastases in colorectal cancer. Yet, with respect to tumor biology and brain metastases, little is known so far. Material and methods Two cohorts, M0 without distant spread and BRA with brain metastases were build. RNA was isolated from paraffin embedded specimen. Gene expression was performed by an RNA NanoString-Analysis using the nCounter® PanCancer Progression Panel by NanoString-Technologies (Hamburg, Germany). Results were analysed by principal component analysis, gene expression and pathway analysis using commonly available databases such as KEGG as benchmark for comparison. Results We were able to determine a gene signature that provides a sophisticated group separation between M0 and BRA using principal component analysis. All genes with strong loading characteristics on principal component 1 were cross-referenced with the subsequently performed accurate gene set enrichment analysis (GSEA). The GSEA revealed a clear dysregulation of the TGFβ pathway in compared cohorts M0 and BRA. Interestingly, the targeted pathways analysis of the identified genes confirmed that in fact almost all strong loading genes of PC1 play a role in the TGFβ pathway. Conclusion Our results suggest the TGFβ pathway as a crucial player in the development of brain metastases in primary CRC. In some types of colorectal cancer, downregulation of the TGFβ pathway might hinder primary colorectal cancer to metastasize to the nervous system. While the paradoxical functioning of the TGFβ pathway is still not fully understood, these shed light on yet another clinical implication of this complex pathway.

Eocene sediments and a fresh to brackish water biota from the early rifting stage of the Upper Rhine Graben (west of oil field Landau, southwest Germany): implications for biostratigraphy, palaeoecology and source rock potential - Christoph Hartkopf-Fröder; Erlend Martini; Claus Heilmann-Clausen; Frank H. Neumann; Peter Schäfer; Heinz Wilkes; Johannes Böcker; Martin Hottenrott (Palaeobiodiversity and Palaeoenvironments, 2024)

Description of a new freshwater bacterium Aquirufa regiilacus sp. nov., classification of the genera Aquirufa, Arundinibacter, Sandaracinomonas, and Tellurirhabdus to the family Spirosomataceae, classification of the genus Chryseotalea to the family Fulvivirgaceae and Litoribacter to the family Cyclobacteriaceae, as well as classification of Litoribacter alkaliphilus as a later heterotypic synonym of Litoribacter ruber - Alexandra Pitt; Stefan Lienbacher; Johanna Schmidt; Meina Neumann-Schaal; Jacqueline Wolf; Martin W. Hahn (Archives of Microbiology, 2024)
Strains LEOWEIH-7C T and LEPPI-3A were isolated from the Leopoldskroner Weiher, a lake located in the city of Salzburg, Austria. 16S rRNA gene similarities and phylogenetic reconstructions with 16S rRNA gene sequences as well as based on genome sequences revealed that the new strains belong to the A. antheringensis branch of the genus Aquirufa . Calculated whole-genome average nucleotide identity (gANI) and digital DNA–DNA hybridization (dDDH) values with the closely related type strains showed that the two strains represent a single new species. The strains grew aerobically and chemoorganotrophically, and the cells were rod shaped, on average 0.8 µm long and 0.3 µm wide, red pigmented and motile by gliding. The genome size of both strains was 2.6 Mbp and the G+C value was 41.9%. The genomes comprised genes predicted for the complete light-harvesting rhodopsin system and various carotenoids. We proposed to establish the name Aquirufa regiilacus sp. nov. for strain LEOWEIH-7C T (=DSM 116390 T = JCM 36347 T ) as the type strain. Strain LEPPI-3A (=DSM 116391 = JCM 36348) also belongs to this new species. The calculated genome-based phylogenetic tree revealed that Aquirufa and some other genera currently allocated in the family Cytophagaceae need a reclassification. Aquirufa , Arundinibacter , Sandaracinomonas , and Tellurirhabdus should be designated to the family Spirosomataceae , the genus Chryseotalea to the family Fulvivirgaceae , and the genus Litoribacter to the family Cyclobacteriaceae . Furthermore, based on calculated gANI and dDDH values, Litoribacter alkaliphilus should be reclassified as a later heterotypic synonym of Litoribacter ruber .

Letter to the editor regarding Collard et al. (2023): “Persistence and mobility (defined as organic-carbon partitioning) do not correlate to the detection of substances found in surface and groundwater: Criticism of the regulatory concept of persistent and mobile substances” - Hans Peter H. Arp; Raoul Wolf; Sarah E. Hale; Sivani Baskaran; Juliane Glüge; Martin Scheringer; Xenia Trier; Ian T. Cousins; Harrie Timmer; Roberta Hofman-Caris; Anna Lennquist; André D. Bannink; et al. (Science of The Total Environment, 2024)

Exploiting synergies between sustainable ammonia and nitric acid production: A techno-economic assessment - Nicole Carina Neumann; David Baumstark; Pablo López Martínez; Nathalie Monnerie; Martin Roeb (Journal of Cleaner Production, 2024)

Histamine H1- and H4-receptor expression in human colon-derived cell lines - Jasper Carsten Schrammel; Martin König; Miriam Frommer; Kaya Saskia Andersen; Marla Kirsten; Roland Seifert; Detlef Neumann; Bastian Schirmer (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
In previous studies, we demonstrated the involvement of H 4 R in inflammatory bowel disease (IBD) and IBD-associated colon cancer in mice and could ascribe H 4 R-mediated histamine function to colon epithelial cells. The transferability of obtained data to humans is however lacking. Functional expression of H 4 R on colon epithelial cells is a prerequisite to pursue the hypothesis of involvement of H 4 R in carcinogenesis. Thus, we here compared the expression of histamine receptor subtypes in a series of cell lines. Out of these, three colon-derived cell lines displaying different combinations of H 1 R and H 4 R expression were submitted to functional analyses. Human hematopoietic HMC-1, HL-60, and U937, lung-derived A549 and Calu-3, and colorectal LoVo, SW 480, Caco-2, HT-29, and HCT116 cells were included in the study. mRNA expression was quantified by RT-qPCR. For functional analyses, Caco-2, HT-29, and HCT116 cells were treated by incubation with 1 – 10 µM histamine in the presence or absence of selective histamine receptor antagonists. Calcium mobilization, cAMP accumulation, and cell proliferation were measured by fluorimetry, mass spectrometry, and real-time bioimpedance measurements, respectively. Histamine receptor expression was heterogeneous in the cell lines tested. In most cell lines, we detected H 1 R mRNA while H 4 R mRNAs were found only occasionally. The colon-derived epithelial cell lines LoVo, SW480, and HT-29 expressed H 1 R mRNA exclusively, while in HCT116 cells H 1 R and H 4 R mRNAs and in CaCo-2 H 2 R mRNA were detectable. Subsequent functional analyses in HT29, Caco-2, and HCT116 cells, however, indicated that only HT-29 responded to histamine stimulation, by means of H 1 R. For a detailed analysis of histamine receptor function, esp. that of H 1 R and H 4 R, in human colon-derived cell lines, the cell lines tested here are not fully convenient unless genetically modified.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Carbapenemase-producing Gram-negative bacteria in hospital wastewater, wastewater treatment plants and surface waters in a metropolitan area in Germany, 2020 - Markus Hoffmann; Martin A. Fischer; Bernd Neumann; Katja Kiesewetter; Ines Hoffmann; Guido Werner; Yvonne Pfeifer; Christoph Lübbert (Science of The Total Environment, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Aquirufa lenticrescens sp. nov. and Aquirufa aurantiipilula sp. nov.: two new species of a lineage of widespread freshwater bacteria - Alexandra Pitt; Ulrike Koll; Johanna Schmidt; Meina Neumann-Schaal; Jacqueline Wolf; Sophia Krausz; Martin W. Hahn (Archives of Microbiology, 2022)
Two bacterial strains, 9H-EGSE T and 15D-MOB T , were isolated from small freshwater habitats located near Salzburg, Austria. They showed the highest 16S rRNA sequence similarities of 100% and 99.9%, respectively, with type strains of species of the genus Aquirufa ( Bacteroidota ). Genome-based phylogenetic reconstructions with 119 amino acid sequences assigned the new taxa to the two distinct branches of the genus Aquirufa . Whole-genome average nucleotide identities were calculated with all possible pairs belonging to the genus. Values between 75.4% and 88.6% revealed that the two new strains represent each a new species. Like all, so far described members of the genus, they grew aerobically and chemoorganotrophically, were rod-shaped, red-pigmented, and motile by gliding, and showed genome sizes of about 3 Mbp and G + C values of about 40%. They could be distinguished by some phenotypic and chemotaxonomic features from their nearest related species. Until now, strain 9H-EGSE T is the only one among the Aquirufa strains which contained traces of MK8 as respiratory quinone, and strain 15D-MOB T is the only one that formed tiny orange globules in liquid medium. The genome of strain 9H-EGSE T comprised genes for the complete light-harvesting rhodopsin / retinal system, in the case of 15D-MOB T genes predicted for a nitrous oxide reductase were present. For the two new species of the genus Aquirufa , we propose to establish the names Aquirufa lenticrescens for strain 9H-EGSE T (= JCM 34077 T = CIP 111926 T ) and Aquirufa aurantiipilula for strain 15D-MOB T (= JCM 34078 T = CIP 111925 T ).

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Correction to: Current evidence on the impact of medication optimization or pharmacological interventions on frailty or aspects of frailty: a systematic review of randomized controlled trials - Farhad Pazan; Mirko Petrovic; Antonio Cherubini; Graziano Onder; Alfonso J. Cruz-Jentoft; Michael Denkinger; Tischa J. M. van der Cammen; Jennifer M. Stevenson; Kinda Ibrahim; Chakravarthi Rajkumar; Marit Stordal Bakken; Jean-Pierre Baeyens; et al. (European Journal of Clinical Pharmacology, 2021)

Genome sequencing in families with congenital limb malformations - Jonas Elsner; Martin A. Mensah; Manuel Holtgrewe; Jakob Hertzberg; Stefania Bigoni; Andreas Busche; Marie Coutelier; Deepthi C. de Silva; Nursel Elçioglu; Isabel Filges; Erica Gerkes; Katta M. Girisha; et al. (Human Genetics, 2021)
The extensive clinical and genetic heterogeneity of congenital limb malformation calls for comprehensive genome-wide analysis of genetic variation. Genome sequencing (GS) has the potential to identify all genetic variants. Here we aim to determine the diagnostic potential of GS as a comprehensive one-test-for-all strategy in a cohort of undiagnosed patients with congenital limb malformations. We collected 69 cases (64 trios, 1 duo, 5 singletons) with congenital limb malformations with no molecular diagnosis after standard clinical genetic testing and performed genome sequencing. We also developed a framework to identify potential noncoding pathogenic variants. We identified likely pathogenic/disease-associated variants in 12 cases (17.4%) including four in known disease genes, and one repeat expansion in HOXD13 . In three unrelated cases with ectrodactyly, we identified likely pathogenic variants in UBA2 , establishing it as a novel disease gene. In addition, we found two complex structural variants (3%). We also identified likely causative variants in three novel high confidence candidate genes. We were not able to identify any noncoding variants. GS is a powerful strategy to identify all types of genomic variants associated with congenital limb malformation, including repeat expansions and complex structural variants missed by standard diagnostic approaches. In this cohort, no causative noncoding SNVs could be identified.

The Indo‐European flyway: Opportunities and constraints reflected by Common Rosefinches breeding across Europe - Simeon Lisovski; Roland Neumann; Tomas Albrecht; Pavel Munclinger; Markus P. Ahola; Silke Bauer; Jaroslav Cepak; Thord Fransson; Sven Jakobsson; Tuomo Jaakkonen; Petr Klvana; Cecilia Kullberg; et al. (Journal of Biogeography, 2021)
Aim The configuration of the earth's landmasses influences global weather systems and spatiotemporal resource availability, thereby shaping biogeographical patterns and migratory routes of animals. Here, we aim to identify potential migratory barriers and corridors, as well as general migration strategies within the understudied Indo‐European flyway. Location Europe, Central Asia. Major taxon studied Common rosefinches. Methods We used a combination of theoretical optimization modelling and empirical tracking of Common Rosefinches ( Carpodacus erythrinus ) breeding across a large latitudinal gradient in Europe. First, we identified optimal migration routes driven by wind and resource availability along the Indo‐European flyway. Second, we tracked rosefinches from five breeding populations using light‐level geolocators. Finally, we compared to what extent empirical tracks overlapped with the modelled optimal routes. Results In autumn, theoretical wind driven migration routes formed a broad‐front corridor connecting Europe and the Indian Subcontinent while the theoretical resource driven routes formed a distinct north‐south divide. The latter pattern also reflected the rosefinch tracks with all but the most southerly breeding birds making a northern detour towards non‐breeding sites in Pakistan and India. In spring, the resource availability model predicted a similar migratory divide, however, the southern route seemed relatively more favourable and closely matched with the optimal wind driven migration routes. Spring tracking data showed larger overlap with the modelled wind driven migration routes compared to the resource driven routes. Main conclusions Optimal wind and resource driven migration routes along the Indo‐European flyway are seasonally specific and to a large extend do not overlap with one another. Under these conditions, migratory birds adopt seasonally distinct migration strategies following energy minimization strategy in autumn, driven by resource availability, and time minimizing strategy in spring, driven by wind conditions. Our optimal migration models can be applied worldwide and used to validate against empirical data to explain large‐scale biogeographic pattern of migratory animals.

Current evidence on the impact of medication optimization or pharmacological interventions on frailty or aspects of frailty: a systematic review of randomized controlled trials - Farhad Pazan; Mirko Petrovic; Antonio Cherubini; Graziano Onder; Alfonso J. Cruz-Jentoft; Michael Denkinger; Tischa J. M. van der Cammen; Jennifer M. Stevenson; Kinda Ibrahim; Chakravarthi Rajkumar; Marit Stordal Bakken; Jean-Pierre Baeyens; et al. (European Journal of Clinical Pharmacology, 2021)
Background Frailty and adverse drug effects are linked in the fact that polypharmacy is correlated with the severity of frailty; however, a causal relation has not been proven in older people with clinically manifest frailty. Methods A literature search was performed in Medline to detect prospective randomized controlled trials (RCTs) testing the effects of pharmacological interventions or medication optimization in older frail adults on comprehensive frailty scores or partial aspects of frailty that were published from January 1998 to October 2019. Results Twenty-five studies were identified, 4 on comprehensive frailty scores and 21 on aspects of frailty. Two trials on comprehensive frailty scores showed positive results on frailty although the contribution of medication review in a multidimensional approach was unclear. In the studies on aspects related to frailty, ten individual drug interventions showed improvement in physical performance, muscle strength or body composition utilizing alfacalcidol, teriparatide, piroxicam, testosterone, recombinant human chorionic gonadotropin, or capromorelin. There were no studies examining negative effects of drugs on frailty. Conclusion So far, data on a causal relationship between drugs and frailty are inconclusive or related to single-drug interventions on partial aspects of frailty. There is a clear need for RCTs on this topic that should be based on a comprehensive, internationally consistent and thus reproducible concept of frailty assessment.

Detection of Colchicum autumnale in drone images, using a machine-learning approach - Lukas Petrich; Georg Lohrmann; Matthias Neumann; Fabio Martin; Andreas Frey; Albert Stoll; Volker Schmidt (Precision Agriculture, 2020)
Colchicum autumnale are toxic autumn-blooming flowering plants, which often grow on extensive meadows and pastures. Thus, they pose a threat to farm animals especially in hay and silage. Intensive grassland management or the use of herbicides could reduce these weeds but environment protection requirements often prohibit these measures. For this reason, a non-chemical site- or plant-specific weed control is sought, which aims only at a small area around the C. autumnale and with low impact on the surrounding flora and fauna. For this purpose, however, the exact locations of the plants must be known. In the present paper, a procedure to locate blooming C. autumnale in high-resolution drone images in the visible light range is presented. This approach relies on convolutional neural networks to detect the flower positions. The training data, which is based on hand-labeled images, is further enhanced through image augmentation. The quality of the detection was evaluated in particular for grassland sites which were not included in the training to get an estimate for how well the detector works on previously unseen sites. In this case, 88.6% of the flowers in the test dataset were detected, which makes it suitable, e.g., for applications where the training is performed by the manufacturer of an automatic treatment tool and where the practitioners apply it to their previously unseen grassland sites.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Comparison of three types of laser optical disdrometers under natural rainfall conditions - Lisbeth Lolk Johannsen; Nives Zambon; Peter Strauss; Tomas Dostal; Martin Neumann; David Zumr; Thomas A. Cochrane; Günter Blöschl; Andreas Klik (Hydrological Sciences Journal, 2020)

Limitations of Weight Velocity Analysis by Commercial Computer Program Growth Analyser Viewer Edition - Martin J. C. van Gemert; Cornelis M. A. Bruijninckx; Ton G. van Leeuwen; H. A. Martino Neumann; Pieter J. J. Sauer (Annals of Biomedical Engineering, 2019)

Mapping interactions between the sustainable development goals: lessons learned and ways forward - Måns Nilsson; Elinor Chisholm; David Griggs; Philippa Howden-Chapman; David McCollum; Peter Messerli; Barbara Neumann; Anne-Sophie Stevance; Martin Visbeck; Mark Stafford-Smith (Sustainability Science, 2018)

Human migration, climate variability, and land degradation: hotspots of socio-ecological pressure in Ethiopia - Kathleen Hermans-Neumann; Joerg Priess; Martin Herold (Regional Environmental Change, 2017)

Unterwasserabgabe nicht aus dem Grundablass — Motive und Folgen alternativer Ausleittiefen - Martin Schultze; Marieke Frassl; Michael Weber; Bertram Boehrer; Karsten Rinke; Ralf Sudbrack; Vincenz Neumann; Hartmut Willmitzer; Markus Möller; Wilfried Scharf (WASSERWIRTSCHAFT, 2016)

Novel antennal lobe substructures revealed in the small hive beetle Aethina tumida - Martin Kollmann; Anna Lena Rupenthal; Peter Neumann; Wolf Huetteroth; Joachim Schachtner (Cell and Tissue Research, 2016)

Aquifer community structure in dependence of lithostratigraphy in groundwater reservoirs - Andrea Beyer; Michael Rzanny; Aileen Weist; Silke Möller; Katja Burow; Falko Gutmann; Stefan Neumann; Julia Lindner; Steffen Müsse; Hanka Brangsch; Jennifer Stoiber-Lipp; Martin Lonschinski; et al. (Environmental Science and Pollution Research, 2015)

Y-P30 promotes axonal growth by stabilizing growth cones - Janine R. Neumann; Suvarna Dash-Wagh; Kay Jüngling; Teresa Tsai; Martin Meschkat; Andrea Räk; Sabine Schönfelder; Christian Riedel; Mohammad I. K. Hamad; Stefan Wiese; Hans-Christian Pape; Kurt Gottmann; et al. (Brain Structure and Function, 2015)

Protein O-glucosylation in Lactobacillus buchneri - Julia Anzengruber; Martin Pabst; Laura Neumann; Gerhard Sekot; Stefan Heinl; Reingard Grabherr; Friedrich Altmann; Paul Messner; Christina Schäffer (Glycoconjugate Journal, 2014)

Forest floor vegetation response to nitrogen deposition in Europe - Thomas Dirnböck; Ulf Grandin; Markus Bernhardt‐Römermann; Burkhardt Beudert; Roberto Canullo; Martin Forsius; Maria‐Theresia Grabner; Maria Holmberg; Sirpa Kleemola; Lars Lundin; Michael Mirtl; Markus Neumann; et al. (Global Change Biology, 2014)
Chronic nitrogen (N) deposition is a threat to biodiversity that results from the eutrophication of ecosystems. We studied long‐term monitoring data from 28 forest sites with a total of 1,335 permanent forest floor vegetation plots from northern Fennoscandia to southern Italy to analyse temporal trends in vascular plant species cover and diversity. We found that the cover of plant species which prefer nutrient‐poor soils (oligotrophic species) decreased the more the measured N deposition exceeded the empirical critical load ( CL ) for eutrophication effects ( P = 0.002). Although species preferring nutrient‐rich sites (eutrophic species) did not experience a significantly increase in cover ( P = 0.440), in comparison to oligotrophic species they had a marginally higher proportion among new occurring species ( P = 0.091). The observed gradual replacement of oligotrophic species by eutrophic species as a response to N deposition seems to be a general pattern, as it was consistent on the European scale. Contrary to species cover changes, neither the decrease in species richness nor of homogeneity correlated with nitrogen CL exceedance (ExCL emp N). We assume that the lack of diversity changes resulted from the restricted time period of our observations. Although existing habitat‐specific empirical CL still hold some uncertainty, we exemplify that they are useful indicators for the sensitivity of forest floor vegetation to N deposition.

Text-speak processing and the sustained attention to response task - James Head; Paul N. Russell; Martin J. Dorahy; Ewald Neumann; William S. Helton (Experimental Brain Research, 2012)

Down-regulation of achaete-scute complex homolog 1 (ASCL1) in neuroblastoma cells induces up-regulation of insulin-like growth factor 2 (IGF2) - Jialing Li; Ingo Neumann; Ines Volkmer; Martin Sebastian Staege (Molecular Biology Reports, 2011)

Methods from the Theory of Random Heterogeneous Media for Quantifying Myocardial Morphology in Normal and Dilated Hearts - Rudolf Karch; Friederike Neumann; Robert Ullrich; Georg Heinze; Josef Neumüller; Bruno K. Podesser; Martin Neumann (Annals of Biomedical Engineering, 2010)

Age dependency of cerebral P-gp function measured with (R)-[11C]verapamil and PET - Martin Bauer; Rudolf Karch; Friederike Neumann; Aiman Abrahim; Claudia C. Wagner; Kurt Kletter; Markus Müller; Markus Zeitlinger; Oliver Langer (European Journal of Clinical Pharmacology, 2009)

Deep-Etching Electron Microscopy of Cells of Magnetospirillum magnetotacticum: Evidence for Filamentous Structures Connecting the Magnetosome Chain to the Cell Surface - Juliana Lopes Martins; Carolina Neumann Keim; Marcos Farina; Bechara Kachar; Ulysses Lins (Current Microbiology, 2007)

Voronoi Polyhedra Analysis of Optimized Arterial Tree Models - Rudolf Karch; Friederike Neumann; Martin Neumann; Paul Szawlowski; Wolfgang Schreiner (Annals of Biomedical Engineering, 2003)

Problem- vs. lecture-based pharmacology teaching in a German medical school - Martin Michel; Angela Bischoff; Dagmar zu Heringdorf; Dietmar Neumann; Karl Jakobs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2002)

Staged Growth of Optimized Arterial Model Trees - Rudolf Karch; Friederike Neumann; Martin Neumann; Wolfgang Schreiner (Annals of Biomedical Engineering, 2000)